The prevalence of capripoxvirus causing lumpy skin disease in beef cattle with no clinical signs on a well-managed cooperative farm - Paitoon Kaewhom; P. Poolsamran; T. Ard-rugsa; Siriwadee Phromnoi; C. Thammakarn; Kanokrat Srikijkasemwat (International Journal of Agricultural Technology, 2025)
Capripoxviruses were confidently detected in cattle, exhibiting a prevalence of 1.17% (9 out of 770 samples). The PCR products from the infected cattle consistently ranged from 1,000 to 1,500 base pairs, even at very low viral loads. Importantly, no significant differences in infection rates were found between the summer and rainy seasons (P > 0.05), and the prevalence was not associated with specific geographical regions or the timing of blood sample collection (P > 0.05). Notably, infected cattle displayed no clinical signs, such as skin nodules, emphasising that the disease can be present without causing visible harm. These findings strongly reinforce the necessity for stringent disease prevention measures in beef cattle production to effectively mitigate potential losses.
Keywords: Poxvirus research and outbreaks; Herpesvirus Infections and Treatments; Plant and Fungal Interactions Research